Contact dermatitis caused by prevention measures during the COVID-19 pandemic: a narrative review - Tang, Huimiao; Wang, Hao; Hamblin, Michael R.; Jiang, Lu; Zhou, Yanjun; Xu, Yidan; Wen, Xiang (Frontiers in Public Health, 2023)
Introduction During the outbreak of Coronavirus disease 2019 (COVID-19), health care workers wore personal protective equipment including masks, gloves and goggles for a long time. In order to reduce the transmission routes of the virus, public places were sprayed with disinfectant. Moreover, the body, hands and clothing were frequently disinfected and washed for hygiene purposes. Studies have shown that these practices could easily irritate the skin and damage the skin barrier. Long-term irritation or exposure to allergens may lead to the occurrence of contact dermatitis (CD). Methods Subject headings were searched via the National Library of Medicine (PubMed) and web of science databases: COVID-19; contact dermatitis; adverse skin reaction; PPE; dermatitis; mask; glory; hand hygiene, disinfection; face shield; goggle; protect cloth. A total of 246 and 646 articles were retrieved from the two databases, respectively. 402 articles remained after removing duplicates. Reviews, non-English articles, articles that could not be accessed to read or did not conform to our topic were excluded. Finally, a total of 32 cross-sectional studies, 9 case reports and 2 randomized controlled trials were included. Discussion This article reviews reports of CD caused by various prevention and hygiene measures during the COVID-19 pandemic. The amount of skin damage caused by COVID-19 prevention measures could be decreased by improved education about skin management.